The Shortcomings of a Partial Release of Employment Protection Laws : The Case of the 2005 French Reform - Cahuc, Pierre (IMF Working Papers; Working Paper ;, 2006)
This paper proposes an ex ante evaluation of the effects of new labor contracts such as the "Contrat Nouvelle Embauche" (CNE) introduced in France in 2005. The lessons we draw are of sufficiently general interest to be applicable to other countries or reforms of employment protection laws. Using a model that captures the characteristics of the French labor market, we simulate the effects of this reform on unemployment, employment, and welfare. We estimate that the CNE will lead to the creation of 70,000 additional jobs in the long run, but at the cost of a slight deterioration in welfare.